WORLD FINANCIAL STABILITY AND DIVERSIFICATION OF CURRENCIES - Bernard Lietaer; Robert E. Ulanovicz; Sally J. Goerner; Nadia McLaren; Y. V. Abramov (Модернизация, инновация, развитие, 2016)
Fundamental laws govern all complex flow systems, including natural ecosystems, economic and financial systems. Natural ecosystems are practical examples of sustainability: enduring, vital, adaptive. The sustainability of any complex flow system can be measured with a single metric as emergent property of its structural diversity and interconnectivity; it requires a balance in emphasis between efficiency and resilience. The urgent message for economics from nature is that the monoculture of national currencies, justified on the basis of market efficiency, generates structural instability in our global financial system. Economic sustainability therefore requires differentiation in types of currencies, specifically through complementary currencies.